RISKS, DANGERS, THREATS OF “CONTINUOUS” E-EDUCATION - T. Yu. Krotenko (Вестник университета, 2020)
The term “digitalization” for a long time settled in the agenda of significant events dedicated to education. The education system, fulfilling the adopted program, should prepare a huge number of schoolchildren, students and workers for life with the indispensable use of information and communication technologies. However, often the actual digitalization is reduced either to the digitization of educational materials and documents in educational structures, or to unhindered access to the Internet. If the request for digitalization is addressed to education, then, being in the pedagogical space, it would be reasonable to first determine what and how to teach. The problem of the lack of a reasonable psychological and pedagogical concept of digital learning, which could be used by the subjects of the educational process as a basic one, is raised in the article.